Reputation evaluation in blockchain based e-commerce system - Sankar Samiksha (Nanyang Technological University, 2024)
In recent years, e-commerce platforms have risen. An important feature in these platforms is the ratings or reviews given to the products sold by the sellers on these platforms. Many buyers rely on these ratings or reviews to make informed decisions on whether to purchase the product. This underscores the importance of online reviews in e-commerce platforms. However, these rating scores are susceptible to adversarial threats.